Visualisasi Bibliometrik Pendekatan Matematis dalam Studi Hukum waris Islam dan Implikasinya terhadap Pendidikan Matematika - Fitria Pujawati; T. Tutut Widiastuti (Mandalika Mathematics and Educations Journal, 2026)
The integration of mathematical approaches into Islamic inheritance law (faraid) plays a crucial role in ensuring accuracy, fairness, and consistency in the distribution of inheritance; however, a systematic mapping of related research remains limited. This study aims to analyze publication trends, conceptual structures, and thematic dynamics of research adopting mathematical approaches in Islamic inheritance law during 2015–2025. A descriptive bibliometric approach was employed, utilizing selected publication metadata retrieved from Google Scholar via the Publish or Perish software and visualized using VOSviewer. The results indicate a gradual increase in publications over the last decade, although mathematical approaches have not yet become a dominant research paradigm. The conceptual structure of the literature is still largely shaped by normative and applicative orientations, with mathematics primarily functioning as a supporting instrument rather than a standalone analytical framework. Network, overlay, and density visualizations further reveal that mathematical integration is a relatively recent and developing trend, characterized by a gradual shift toward more quantitative and interdisciplinary perspectives. These findings highlight opportunities for future research to strengthen mathematics as a more substantive analytical foundation in Islamic inheritance law and to support its integration into context-based mathematics education.